Subcutaneous Fluid Administration: A Potentially Useful Tool in Prehospital Care - Annette O. Arthur; Jeffrey M. Goodloe; Stephen H. Thomas (Emergency Medicine International)
Mass casualty incidents (MCIs) and disaster medical situations are ideal settings in which there is need for a novel approach to infusing fluids and medications into a patient’s intravascular space. An attractive new approach would avoid the potentially time-consuming needlestick and venous cannulation requiring a trained practitioner. In multiple-patient situations, trained practitioners are not always available in sufficient numbers to enable timely placement of intravenous catheters. The novel approach for intravascular space infusion, described in this paper involves the preadministration of the enzyme, human recombinant hyaluronidase (HRH), into the subcutaneous (SC) space, via an indwelling catheter. The enzyme “loosens” the SC space effectively enhancing the absorption of fluids and medication.